Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0005986.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Limb Development Anomalies: Genetics

Abstract: Congenital limb malformations range from reduction defects to subtle digit anomalies (number/length/anatomy). Their prevalence is evaluated from 1.3‰ to 1.9‰ neonates. They can be classified as disruption anomalies and genetic malformations. The later are due to limb development gene function alteration and may be isolated or associated with other malformations. The genes implicated in the limb bud development are numerous. They work together to trigger limb bud growth (proximodistal axis), polaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Some of them have a genetic basis and, currently, more than 150 genes or regulatory regions are known to be implicated in limb malformations (Manouvrier‐Hanu, Holder‐Espinasse, & Lyonnet, ; Manouvrier‐Hanu, Petit, Holder‐Espinasse, & Escande‐Narducci, ; Zuniga, Zeller, & Probst, ). In most cases, the responsible genetic anomaly is a single nucleotide variation (SNV) (Manouvrier‐Hanu et al, ). However, copy‐number variations (CNVs) involving genes or noncoding regulatory elements are also a major cause of CLM (Flottmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have a genetic basis and, currently, more than 150 genes or regulatory regions are known to be implicated in limb malformations (Manouvrier‐Hanu, Holder‐Espinasse, & Lyonnet, ; Manouvrier‐Hanu, Petit, Holder‐Espinasse, & Escande‐Narducci, ; Zuniga, Zeller, & Probst, ). In most cases, the responsible genetic anomaly is a single nucleotide variation (SNV) (Manouvrier‐Hanu et al, ). However, copy‐number variations (CNVs) involving genes or noncoding regulatory elements are also a major cause of CLM (Flottmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Failure of differentiation and duplication are the most frequent anomalies with polydactyly is the most common individual diagnosis with an incidence of about 1 per 1000 live births. [ 2 8 ] This study also revealed that failure of differentiation and duplication anomalies were most frequent deformities (90.6%) with polydactyly was the most common anomaly encountered.…”
Section: Discussionmentioning
confidence: 58%
“…[ 1 ] Congenital hand anomalies rank the second most frequent malformation affecting the human body. [ 2 ] They are encountered in 0.1–0.2% of all newborns. [ 3 ] males are more commonly affected with polydactyly and syndactyly are the most common anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5 The identification of genes for malformation syndrome provides an opportunity to peep into the complex developmental processes involved in limb development. This is because they are caused by mutations that affect important signaling pathways repetitively used during embryonic development at different times and different locations.…”
Section: Resultsmentioning
confidence: 99%